Four princes : Henry VIII, Francis I, Charles V, Suleiman the Magnificent and the obsessions that forged modern Europe - Norwich, John Julius, 1929-2018 (Atlantic Monthly Press, 2017)
"John Julius Norwich--who the Wall Street Journal called "the very model of a popular historian"--has crafted a big, bold tapestry of the early sixteenth century, when Europe and the Middle East were overshadowed by a quartet of legendary rulers, all born within a ten-year period: Francis I of France, the personification of the Renaissance, who became a highly influential patron of the arts and education. Henry VIII, who was not expected to inherit the throne but embraced the role with gusto, broke with the Roman Catholic Church and appointed himself head of the Church of England. Charles V, the most powerful and industrious man at the time, was unanimously elected Holy Roman Emperor. Suleiman the Magnificent stood apart as a Muslim, and brought the Ottoman Empire to its apogee of political, military, and economic power. Against the vibrant background of the Renaissance, these four men laid the foundations for modern Europe and the Middle East. Their relations shifted dramatically, from hostile and competitive to friendly and supportive, while they collectively impacted the culture, religion, and politics of their respective domains. With remarkable expertise and flair, John Julius Norwich delves into this fascinating slice of world history, bringing the past to vivid life. His engaging, distinctive blend of erudition and brio indelibly portrays four dynamic characters, their incredible achievements, and the colorful surroundings in which they lived, while deftly examining the influence that each one had on the reigns of the others."--Provided by publisher.